(untitled) (Communications in Computational Physics, 2011)
A quasi non-overlapping hybrid scheme that combines the finite-difference time-domain (FDTD) method and the finite-element time-domain (FETD) method with nonconforming meshes is developed for time-domain solutions of Maxwell's equations. The FETD method uses mixed-order basis functions for electric and magnetic fields, while the FDTD method uses the traditional Yee's grid; the two methods are joined by a buffer zone with the FETD method and the discontinuous Galerkin method is used for the domain decomposition in the FETD subdomains. The main features of this technique is that it allows non-conforming meshes and an arbitrary numbers of FETD and FDTD subdomains. The hybrid method is completely stable for the time steps up to the stability limit for the FDTD method and FETD method. Numerical results demonstrate the validity of this technique.